2015
DOI: 10.1001/jamapsychiatry.2015.2146
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Group Psychotherapy, Individual Counseling, Methylphenidate, and Placebo in the Treatment of Adult Attention-Deficit/Hyperactivity Disorder

Abstract: ; for the Comparison of Methylphenidate and Psychotherapy in Adult ADHD Study (COMPAS) Consortium IMPORTANCE Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder with high prevalence in adulthood. There is a recognized need to assess the efficacy of psychotherapy in adult ADHD. OBJECTIVE To evaluate the efficacy of cognitive behavioral group psychotherapy (GPT) compared with individual clinical management (CM) and that of methylphenidate hydrochloride compared with placebo. DESIGN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
148
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(173 citation statements)
references
References 47 publications
(36 reference statements)
15
148
2
7
Order By: Relevance
“…In adults with ADHD, two single studies on methylphenidate added on highly structured group CBT versus non-specific clinical management, provided discordant results 49 50. However, there is no evidence from systematic reviews, so that this issue needs to be further explored 38 41 51…”
Section: Resultsmentioning
confidence: 99%
“…In adults with ADHD, two single studies on methylphenidate added on highly structured group CBT versus non-specific clinical management, provided discordant results 49 50. However, there is no evidence from systematic reviews, so that this issue needs to be further explored 38 41 51…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Treatments were allocated with a 1:1:1:1 ratio, stratified by centre. 31 Patients and therapists were blinded for medication, but were aware of the assignment to either GPT or CM. However, the observers rating the symptoms of ADHD (using the Conner Adult ADHD Rating Scale [CAARS], the Diagnostic checklist for diagnosis of ADHD in adults and the Clinical Global Impressions Scale) were blind to the allocation of treatment.…”
Section: Randomization and Maskingmentioning
confidence: 99%
“…29,30 The results of the clinical trial are published elsewhere. 31 Neuro imaging measurements were obtained at baseline (week 0), after 3 months (week 13) and after 1 year (week 52).…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial with 419 patients, cognitive behaviour group treatment (GPT) was compared to clinical management (CM) for twelve weeks and thereafter every month for nine months. In addition, patients in the study received either central stimulants or a placebo (Philipsen et al, 2015). The results showed that pharmacological treatment was effective for core symptoms of ADHD and after three months, CM appeared superior to the structured group treatment, but long-term effects favoured GPT, especially when measuring patients´ general wellbeing, coping skills, self-esteem and acceptance.…”
Section: Psychotherapy For Adhdmentioning
confidence: 99%
“…Evidence for usefulness of psychosocial treatment in adult ADHD is inconclusive (Philipsen et al, 2015) but in combination with pharmacological medication there is evidence of efficaciousness (Skokauskas, McNicholas, Masaud, & Frodl, 2011). In a randomized controlled trial with 419 patients, cognitive behaviour group treatment (GPT) was compared to clinical management (CM) for twelve weeks and thereafter every month for nine months.…”
Section: Psychotherapy For Adhdmentioning
confidence: 99%